Evaluation of an Integrated Health Promotion Program for a low‐income urban population: Findings and lessons learned. Issue 4 (20th November 2020) - Weiss, Linda; Quint, Elizabeth; Leto, Christopher; Vaughn, Ivana; Redrovan, Alba; Fernandes, Marta; Lamourt, Kianna; Edgar, Colin; Reso, Ada
Abstract: Objectives: To evaluate a multicomponent pilot program for low‐income individuals with, or at risk for, hypertension, diabetes, and/or overweight. Design: Pre‐post evaluation including baseline and follow‐up assessments, satisfaction surveys, program utilization data, and focus groups. Sample: The evaluation included 138 participants. The majority were Latinx (88%), female (82%), born outside the United States (80%), and had not graduated from high school (52%). The most common health conditions were hypertension (59%), overweight or obesity (55%), high cholesterol (53%), and diabetes (34%). Measurements: Engagement in program activities, health indicators (e.g., blood pressure), and behavior change. Qualitative data focused on perceptions of the program and its impacts. Intervention: The program offered a number of health promotion services, including consultation with a nurse and a community health worker (CHW), health and nutrition talks, subsidized farm shares, cooking classes, exercise classes, and home visits. Results: There were improvements in general health, blood pressure, and knowledge and behavior related to disease management and healthy eating. Conclusions: Program success was attributed to the wide range of complementary program components. The staffing model was also a strength: the CHW/nurse collaboration combined clinical expertise with cultural, language, and community knowledge to create a program that was accessible and empowering.